An assessment on the impacts of government food aid projects in promoting household food security: the case of drought relief programmes in Mutare District Ward 15 2013 to 2016. - Munoangira, Desire (Midlands State University, 2019)
The study was carried out in Mutare District ward 15 from 2013-2016. The aim of the study was to assess the impacts of Government Food Aid projects in promoting household food security paying particular attention on the Drought Relief Programmes. The study sampled 52 households using simple random sampling who are the beneficiaries of food aid. The study also sampled 10 government officials using purposive sampling who have been implementing the programme. Government Food aid programmes have been a major aspect of debate in the 21st C. Some have argued that food aid projects have become a strong tool hedging against cases of widespread hunger. Others have indicated that food aid programmes have done less towards ensuring household food security. In this research, data was collected using interviews, questionnaires and documents that were analysed using thematic analyses, content analyses and Statistical Package Social Sciences. The results show that Government programmes are doing much effort to try to alleviate poverty in rural households but there are a number of factors militating against the success of these projects. These factors include nepotism, corruption, favouritism, lack of funds, and lack of integration between project implementers among other factors. Hence, for the project to meet its intended objectives of ensuring household food security, the government is recommended to address various issues. These issues include the facilitation of the selection process of beneficiaries, source enough funds towards the success of the project, and educate people on the importance of the programme to cab cases of favouritism and nepotism and to conduct post-monitoring visits. In pursuit of these recommendations, there is no doubt that Government Food Aid Projects will reach an envisaged scale.